Landscape Design Software: Evaluation and Recommendations for Homeowners - Gail Hansen; Smith Watkins; Sydney Park Brown (EDIS)
Homeowners who are computer literate and want to improve their landscapes often consider purchasing software so that they can create the design themselves and save money. To help you select a program from the dozens that are available, each with different levels of cost and difficulty, UF/IFAS scientists tested seven popular do-it-yourself programs, compared them to a professional landscape design software program, and rated them for quality of features and ease-of-use. This 9-page fact sheet will help you estimate costs, ensure compatibility with your Windows-based or Apple-based operating system, and compare reviews from consumer websites so that you can choose the software that best fits your needs. Written by Gail Hansen, Smith Watkins, and Sydney Park Brown, and published by the Department of Environmental Horticulture, October 2015.